Unsuspecting Lead Points Causing Nonobstructing Intussusceptions in Pediatric Patients Presenting with Chronic Pain Abdomen - Jain, Garima; Royal, Nirmala; Sharma, Pramila; Bhandari, Anu; Mendiratta, Kuldeep (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Intussusception is one of the common causes of bowel obstruction in pediatric age group and is of idiopathic variety in most of the cases. Nonobstructing intussusception presenting with nonspecific symptoms (or chronic pain abdomen) is rare and usually clinically misdiagnosed/difficult to diagnose. The authors present a pictorial review of 10 cases of pediatric nonobstructing intussusception presenting with acute/chronic abdominal pain which were not suspected clinically but diagnosed with a pathologic lead point radiologically.
Keywords: pediatric; nonobstructing intussusception; pathologic lead point